Urgent Cardiosurgical Treatment of a Military Servant with a Moving Thrombus in the Area of the Left Ventricular Apical Aneurysm (Case Report) - Gogayeva, Olena K.; Nudchenko, Oleksandr O.; Malysheva, Tetiana A.; Shnaider, Liudmyla M.; Tertychna, Anastasiia S.; Stavinchuk, Victoria I.; Rudenko, Serhii A. (Ukrainian Journal of Cardiovascular Surgery, 2024)
Against the background of military operations, post-traumatic stress disorder, the progression of the atherosclerotic process is observed, which can lead to myocardial infarction even in young people. Left ventricular aneurysm (LVA) in military personnel is the result of untimely revascularization of an infarct-related artery, gunshot wound to the heart, chest trauma, etc. The presence of a dyskinetic area promotes formation of blood clots in the LVA cavity. LVA thrombosis is associated with an increased risk of embolism, ischemic stroke, and death. Case description. A 37-year-old military servant A. was urgently hospitalized to the National Amosov Institute of Cardiovascular Surgery of the National Academy of Medical Sciences of Ukraine with a mobile thrombus in the area of LVA, size 4.5 x 3 cm, with signs of lysis and a threat of separation according to echo data. The patient was found to suffer Q-wave myocardial infarction 5 months ago; at the time of examination there was decompensation of the condition and a decrease in the left ventricular contractility to 34%. The patient underwent urgent operation: on-pump coronary artery bypass grafting, LVA resection with thrombectomy. The duration of the operation was 7 hours, the aortic cross-clamp time was 53 minutes, the perfusion time was 93 minutes, the blood loss was 500 ml. The postoperative period was uneventful. The patient was discharged on the 7th day with improvement, the ejection fraction was 40%. Conclusion. The lack of an opportunity to conduct timely electrocardiography and echo for military personnel with acute chest pain reduces the chances of diagnosis and treatment of myocardial infarction within the therapeutic window, which leads to the occurrence of complicated forms of coronary heart disease, namely LVA. Echo is of crucial importance in deciding on emergency cardiac surgery for thrombosed LVA.